2019
DOI: 10.3390/brainsci9060135
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Phenomenological Properties of Odor-Evoked Autobiographical Memories in Alzheimer’s Disease

Abstract: Autobiographical memory, which contains all personal memories relative to our identity, has been found to be impaired in Alzheimer’ Disease (AD). Recent research has demonstrated that odor may serve as a powerful cue for the recovery of autobiographical memories in AD. Building on this research, we investigated emotional characteristics (arousal and valence) and subjective reliving of odor-evoked autobiographical memories in AD. We also investigated the relationship between these characteristics and depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 74 publications
3
25
0
Order By: Relevance
“…Studies along this line could also stimulate applied research in clinical psychology, and especially the development of reminiscence therapies ( Duru Aşiret and Kapucu, 2016 ; Glachet et al, 2018 ; Mileski et al, 2018 ; Kirk et al, 2019 ). Among the different approaches, the use of sensory-based reminiscence therapy appears particularly promising since sensory cues could provide a more direct access to autobiographical memories and thus minimize the demand on executive control processes ( Kirk and Berntsen, 2018 ; Glachet and El Haj, 2019 ). For instance, the use of odors or music cues have been found to enhance the specificity and the phenomenological experience of memories evoked by people with Alzheimer’s disease ( El Haj et al, 2012 ; Glachet and El Haj, 2019 ), and odors also improved the access to self-concepts ( Glachet and El Haj, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies along this line could also stimulate applied research in clinical psychology, and especially the development of reminiscence therapies ( Duru Aşiret and Kapucu, 2016 ; Glachet et al, 2018 ; Mileski et al, 2018 ; Kirk et al, 2019 ). Among the different approaches, the use of sensory-based reminiscence therapy appears particularly promising since sensory cues could provide a more direct access to autobiographical memories and thus minimize the demand on executive control processes ( Kirk and Berntsen, 2018 ; Glachet and El Haj, 2019 ). For instance, the use of odors or music cues have been found to enhance the specificity and the phenomenological experience of memories evoked by people with Alzheimer’s disease ( El Haj et al, 2012 ; Glachet and El Haj, 2019 ), and odors also improved the access to self-concepts ( Glachet and El Haj, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the different approaches, the use of sensory-based reminiscence therapy appears particularly promising since sensory cues could provide a more direct access to autobiographical memories and thus minimize the demand on executive control processes ( Kirk and Berntsen, 2018 ; Glachet and El Haj, 2019 ). For instance, the use of odors or music cues have been found to enhance the specificity and the phenomenological experience of memories evoked by people with Alzheimer’s disease ( El Haj et al, 2012 ; Glachet and El Haj, 2019 ), and odors also improved the access to self-concepts ( Glachet and El Haj, 2020 ). These previous results thus contrast with some of our current findings in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…As the French author Marcel Proust described long ago (Proust, 1927), referenced in his work A la Recherche du Temps Perdu which translates to In Search of Lost Time -"Yet a single scent already breathed long ago, may once again both be in the present and the past, be real without being present". Sensory experiences like olfaction and gustation have the ability to produce the evocation of vivid autobiographical memories of the distant past (Toffolo et al, Grella et al, 15 2012;Zucco et al, 2012;Daniels and Vermetten, 2016;Glachet and El Haj, 2019). This spontaneous process which we have all experienced at one time or another is often referred to as the Proust Phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only five studies have examined the impact of odor on autobiographical remembering in AD [123,[160][161][162][163]. All studies have demonstrated the positive effects of odor on personal event memories.…”
Section: Emotional Sensorial Stimulations and Self-consciousness In Amentioning
confidence: 99%
“…The team of Dr. Glachet [162] also found a positive effect of odor exposure on recent autobiographical memories in AD. Additionally, Glachet & El Haj [161] investigated emotional characteristics (arousal and valence) and subjective reliving of odor-evoked autobiographical memories in AD. They observed higher arousal, subjective reliving, and more positive memories after odor exposure compared with the odor-free condition only in the AD group.…”
Section: Emotional Sensorial Stimulations and Self-consciousness In Amentioning
confidence: 99%